Herniorrafia em bovino com utilização do saco herniário: Descrição de um caso - Sampaio, Romeu; Titton Ranzani, José Joaquim; Junqueira del Carlo, Ricardo (Revista Ceres, 2025)
A surgical tecnique is described as employed for the reduction of a recidivant umbilical hernia in a calf by utilization of a hernial sac originally used by SILVA (9) for a human patient.